The improvement of competitive saprophytic capabilities of Trichoderma species through the use of chemical mutagens - Singh,Rashmi (2016)
Abstract The antagonistic potential of Trichoderma strains was assayed by studying the effect of their culture filtrate on the radial growth of Sclerotium rolfsii, the causal agent of chickpea collar rot. Trichoderma harzianum-1432 (42.2%) and Trichoderma atroviride (40.3%) were found to be strong antagonists. To enhance their antagonistic potential, mutagenesis of these two selected strains was performed. Two mutants, Th-m1 and T. atroviride m1, were found to be more effective than their parent strains. The enzymatic activities of the selected parent and mutant strains were assayed, and although both mutants were found to have enhanced enzymatic activities compared to their respective parent strains, Th-m1 possessed the maximum cellulase (5.69 U/mL) and β-1,3-glucanase activity (61.9 U/mL). Th-m1 also showed high competitive saprophytic ability (CSA) among all of the selected parent and mutant strains, and during field experiments, Th-m1 was found to successfully possess enhanced disease control (82.9%).